PENGARUH JARAK KANDANG TERNAK TERHADAP TOTAL COLIFORM PADA AIR SUMUR GALI DI DESA KLAMBIR - Yusdiah Sari; Nurbaity Situmorang (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2020)
Clean water needs one of which can be obtained through a dug well. As for things that need to be considered in the use of dug wells that meet health requirements. This is intended to minimize the occurrence of well water contamination caused by contaminants that exist around the dug well. The purpose of conducting this research was to analyze the influence caused by the dintance of the cattle pen with the presence of total Coliform bacteria in the dug wells of Klambir Village. This study used an observational analytic method with a cross sectional design. The study were used 35 samples and it was determined by simple random sampling. The results obtained from the research that from 35 samples examined entirely contain Coliform. In detail can be explained that as much as 22 wells (62.9%) had total coliforms> 50/100 ml and 13 wells (37.1%) had total coliforms ≤ 50/100 ml of water. The results of multiple logistic regression analysis showed that there was an effect of enclosure distance on total coliform in dug well water.